First thing you need to realise is that x/y multiplied by something is the same as x multiplied by that something, ALL divided by y
from here we can think of this as 3(2x-1) all over 5 = 1(5x-3) all over 4,
now we can start by expanding the left side, so it will equal 6x-3 all over 5 = 5x-3 all over 4
Now multiplying both sides by 5 to get rid of the divided by 5 on the left hand....
6x-3 = 25x-15 all over 4
We then multiply both sides by 4 to eliminate the divided by 4 on the right hand side....
We get 24x-12=25x-15
Now subtract 25x from both sides....
-1x = -3
Therefore diving both sides by -1 we get x=3